HAK ASASI MANUSIA DALAM PANDANGAN ISLAM - Pitriani, Pitriani (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2014)
Normally, the position of the human person with all the rights of the most fundamental has gained recognition in the Declaration and the International Covenants. Human rights have become values and norms in international relations. This is shown by the agreement of all countries, at least in countries that are members of the United Nations to the United Nations Charter, the Universal Declaration of Human Rights (1948). Islam as a religion and its teachings are universal and comprehensive, encompassing faith, worship, and muamalat, each of which contains the doctrine of the faith; religious dimension to the teachings of the mechanisms of human devotion to God; with either the doctrine of mans relationship with fellow humans and to the environment. Each dimension is based on the teachings of the provisions referred to by the term Sharia or Islamic jurisprudence. In the context of law or jurisprudence there are teachings on Human Rights (HAM). The existence of the doctrine of human rights in Islam shows that Islam as a religion has placed man as honorable and noble creatures. Therefore, the protection and respect for the human being is the claim of Islam itself must be carried out by Muslims against fellow human beings without exception.Secara normatif, kedudukan pribadi manusia dengan segala hak-haknya yang paling asasi telah memperoleh pengakuan dalam Deklarasi dan Kovenan-kovenan internasional. Hak-hak asasi manusia telah menjadi nilai dan norma dalam hubungan internasional. Hal ini ditunjukkan oleh persetujuan semua negara, setidak-tidaknya negara-negara yang menjadi anggota PBB terhadap piagam PBB, Deklarasi Universal tentang Hak-Hak Asasi Manusia (1948).Islam sebagai sebuah agama dengan ajarannya yang universal dan komprehensif meliputi akidah, ibadah, dan muâamalat, yang masing-masing memuat ajaran tentang keimanan; dimensi ibadah memuat ajaran tentang mekanismeÂ  pengabdian manusia terhadap Allah; dengan memuat ajaran tentangÂ  hubungan manusia dengan sesama manusia maupun dengan alam sekitar. Kesemua demensi ajaran tersebut dilandasi oleh ketentuan-ketentuan yang disebut dengan istilah syariâah atau fikih.Dalam konteks syariâat atau fikih itulah terdapat ajaran tentang Hak Asasi Manusia (HAM).Adanya ajaran tentang HAM dalam Islam menunjukkan bahwa Islam sebagai agama telah menempatkan manusia sebagai makhluk terhormat dan mulia.Karena itu, perlindungan dan penghormatan terhadap manusia merupakan tuntutan dari ajaran Islam itu sendiri yang wajib dilaksanakan oleh umatnya terhadap sesama manusia tanpa kecuali.